Melanins in fungi: Types, localization and putative biological roles - Toledo, Andrea Vanesa (2017)
Melanin is a secondary metabolite made up by complex heterogeneous polymers. Several classes of fungal melanins have been described like γ-glutaminyl-3,4-dihydroxy-benzene (GDHB)-, L-DOPA-(eumelanin), DHN-, catechol-melanin, pyomelanin, p-aminophenol (PAP)-melanin, heterogeneous melanins as well as two others based on 5-deoxybostrycoidin and aspulvinone E. They have been mostly localized in cell walls of different structures of fungi, which suggest that they play a different biological role. They have been related mostly with morphogenesis, stress resistance, virulence and energy transduction. However, an enormous amount of work remains to be done to clarify, among other things, the role melanins play in fungi.